Nurses' Perspectives on Postpartum Pain Management - Benjamin R. Loomis; Lynn M. Yee; Lauren Hayes; Nevert Badreldin (Mary Ann Liebert, 2022)
Introduction: There is variation in postpartum opioid use by prescriber characteristics that cannot be explained by patient or birth factors. Thus, our objective was to evaluate nursing training, clinical practices, and perspectives on opioid use for postpartum pain management. Materials and Methods: In this survey study, postpartum bedside nurses at a single, large academic center were asked about training, factors influencing clinical decisions, and viewpoints regarding pain management and opioid use. Findings were summarized using descriptive analyses. Results: A total of 92 nurses completed the survey. A majority (77%) reported having received some formal training on opioid use for pain management. About a quarter (25.7%) felt their training was not adequate. Regarding clinical practices, the majority (71% and 70%, respectively) reported that ?routine habit? and ?patient preference? most influenced the type and amount of pain medication they administered. Finally, nurses' perspectives on pain management demonstrated a wide range of beliefs. Most nurses strongly agreed with the importance of maximizing nonopioid pain medication before opioid administration. The majority agreed that patient-reported pain score is important to consider when deciding to administer opioids. Conversely, most nurses disagreed that patients should be encouraged to endure as much pain as possible before using an opioid. Similarly, beliefs about the reliability of use of vital signs in assessing pain intensity varied widely. Conclusions: Bedside nurses rely on routine habits, patient preference, and patient-reported pain score when administering opioids for postpartum pain management. Increased training opportunities to improve consistency and standardization of opioid administration may be beneficial.